Development of a single-stage mainstream anammox process using a sponge-bed trickling filter. Issue 19 (24th August 2021) - Watari, Takahiro; Vazquez, Carlos Lopez; Hatamoto, Masashi; Yamaguchi, Takashi; van Lier, Jules B.
ABSTRACT: Anaerobic ammonia oxidation to nitrogen gas using nitrite as the electron acceptor (anammox process) is considered a cost-effective solution for nitrogen removal after an anaerobic pre-treatment process. In this study, we conducted a laboratory-scale experiment to develop a single-stage partial nitritation–anammox process in a sponge-based trickling filter (STF) reactor, inoculated with anammox sludge, simulating the treatment of anaerobically pretreated concentrated domestic sewage without mechanical oxygen control. The influent ammonia concentration was 100 mg-N·L −1 . The KL a of the STF reactor was higher than those observed for conventional activated sludge processes. The STF reactor performed at 89.8 ± 8.2% and 42.7 ± 16.9% ammonia and TN removal efficiency, respectively, with a nitrogen loading rate of 0.55 ± 0.20 kg-N·m −3 ·day −1 calculated based on sponge volume. Microbial community analysis of the STF-retained sludge indicated that both autotrophic and heterotrophic nitrogen removal occurred in the reactor. GRAPHICAL ABSTRACT: UF0001